Sleep disorders in acting military services: comparative analysis of psychopharmacological and psychotherapeutic correction - Kurilo, V. O.; Guk, G. V.; Курило, В. А.; Гук, Г. В.; Курило, Віталій Олексійович; Гук, Галина Валеріївна (Минск : Профессиональные издания, 2021)
Abstract. The mental health of military personnel of the Armed Forces of Ukraine is of a particular importance in the context of active hostilities in the country. Our attention is turned to the problem of frequently detected inorganic sleep disorders in patients of Zaporizhzhia military hospital, which are often associated with non-psychotic mental disorders of subclinical or clinical severity, which gives us a purpose to consider dyssomnic syndrome as a signifi cant risk factor for adverse mental health outcomes and fi nd new ergonomic options in sleep disorders management. The purpose of the paper is to evaluate the clinical signifi cance of new developed psychotherapeutic approach to inorganic sleep disorders management in comparison with standard pharmacological treatment. On the base of Zaporizhzhia Military Hospital, Ukraine, with the informed consent, 44 acting military servicemen of the Armed Forces of Ukraine (males aged 19.4–58.1) with inorganic sleep disorders were included into 2-cohort clinical trial during their inpatient treatment. 20 patients, who chose psychotherapeutic treatment, formed the Cohort 1 of the study. Cohort 2 was formed with 24 patients, who preferred standard management with benzodiazepines. All participants underwent qualitative (clinical interview) and quantitative (Pittsburg Sleep Quality Index – PSQI, Epworth sleepiness scale rate) assessment of sleep characteristics twice – before treatment and just before discharge. Clinical-psychopathological, psychodiagnostic and statistical methods were used in the study. The subjects from both cohorts showed sleeping relief and reported decrease of falling asleep time, the frequency of nocturnal wake-ups and early rises. It was objectifi ed by PSQI fall from average 11.74±3.12 and 11.79±3.23 before treatment to 6.12±3.42 and 6.04±3.12 just before discharge from the hospital in the Cohort 1 and Cohort 2, respectively. Sleep improvement came about three days earlier in the Cohort 2. An average treatment duration was 8.20 ± 3.83 days. At the same time, 9 patients (37.5 %) of this group noted more pronounced daytime sleepiness in comparison with the Cohort 1 participants, whose sleep improvement developed later. However, it was associated with better concentration and alertness throughout the day. The new developed method of psychotherapeutic correction of inorganic sleep disorders shows almost equivalent eff ectiveness in comparison with the standard drug treatment. Meanwhile, it has certain benefi ts for acting military servicemen, specifi cally absence of heaviness in the head or pronounced daytime sleepiness and better concentration rate as these characteristics can signifi cantly aff ect the quality of combat missions. Резюме. Психическое здоровье военнослужащих Вооруженных Сил Украины имеет особое значение в условиях активных боевых действий в стране. Наше внимание привлекает проблема частого выявления нарушений сна неорганического генеза у пациентов Запорожского военного госпиталя, нередко в коморбидности с непсихотическими психическими расстройствами субклинического или клинического уровня. Это позволяет нам рассматривать диссомнический синдром как существенный фактор риска неблагоприятных последствий для психического здоровья, учитывая который целесообразно искать новые эргономичные методы лечения нарушений сна. Целью статьи является оценка клинической эффективности новой разработанной психотерапевтической методики коррекции неорганических нарушений сна в сравнении со стандартным фармакологическим лечением. В 2-когортное клиническое исследование на базе Запорожского военного госпиталя (Украина) на основании информированного согласия во время стационарного лечения было включено 44 действующих военнослужащих Вооруженных Сил Украины с неорганическими нарушениями сна. Общую выборку составили мужчины в возрасте от 19,4 до 58,1 года. Двадцать пациентов, которые выбрали психотерапевтическое лечение, сформировали группу исследования 1 (ГИ-1). Вторая группа исследования (ГИ-2) была сформирована из 24 пациентов, которые предпочли стандартное лечение бензодиазепинами. Все участники прошли качественную (клиническое интервью) и количественную (индекс качества сна Питтсбурга – PSQI, показатель сонливости по шкале Эпворта) оценку характеристик сна дважды – перед лечением и непосредственно перед выпиской. В исследовании использовались клинико-психопатологические, психодиагностические и статистические методы. Пациенты из обеих групп исследования сообщали об улучшении сна и об уменьшении времени засыпания, частоты ночных пробуждений и ранних подъемов. Объективизировалось данное улучшение падением PSQI со среднего значения 11,74±3,12 и 11,79±3,23 до лечения до 6,12±3,42 и 6,04±3,12 непосредственно перед выпиской из больницы в ГИ-1 и ГИ-2 соответственно. Улучшение сна наступало примерно на три дня раньше в ГИ-2 при средней продолжительности лечения 8,20±3,83 дня. В то же время 9 пациентов (37,5%) этой группы отметили более выраженную дневную сонливость по сравнению с участниками ГИ-1, у которых улучшение сна наступало позже, однако сопровождалось лучшей концентрацией и скоростью реакции в течение дня. Новая разработанная методика психотерапевтической коррекции неорганических нарушений сна демонстрирует почти равнозначную эффективность по сравнению со стандартным медикаментозным лечением. Вместе с тем она имеет определенные преимущества для действующих военнослужащих, например, отсутствие тяжести в голове или выраженной дневной сонливости и наличие высокого уровня концентрации внимания, поскольку эти показатели могут существенно повлиять на качество выполнения боевых задач.
Нарушение сна во время военной службы: сравнительный анализ психофармакологической и психотерапевтической коррекции
Keywords: sleep disorder; military servicemen; combatants; psychotherapeutic treatment; mental disorder; risk factor; mental health; benzodiazepines; расстройство сна; военнослужащие; участники боевых действий; психотерапевтическое лечение; психическое расстройство; фактор риска; психическое здоровье; бензодиазепины